Outer rotor wound field flux switching machine for In‐wheel direct drive application. Issue 6 (18th April 2019) - Ahmad, Naseer; Khan, Faisal; Ali, Hazrat; Ishaq, Samra; Sulaiman, Erwan
Abstract : Nowadays the flux switching machines offer pivotal role in high speed applications. The flux sources (field excitation coil and armature winding or permanent magnet) are confined to the stator leaving rotor completely passive, and thus making the flux switching machine (FSM) more suitable for industrial applications. This paper emphasizes salient rotor pole and non‐overlapping windings embedded in electrical machine design possess some pertinent features such as reduced copper losses, low‐cost, and usage in high speed applications. The proposed design is analyzed for coil test analysis and flux linkage and torque. On the basis of the analysis performed, it is clear that 12‐slot/13‐pole has low cogging torque, high flux linkage, and maximum torque, compared with other topologies of outer rotor field excitation FSM. A deterministic optimization technique is adopted to enhance the performance of 12‐slot/13‐pole design. Further, finite element analysis (FEA) results are verified through Global Reluctance Network (GRN) methodology, which show close resemblance with error less than 1.2%. Hence, it validates the proposed design for outer rotor field excitation FSM direct drive application. The proposed design for hybrid electric vehicle torque characteristic is compared with existing interior permanent magnet synchronous machine (IPMSM) and 6‐slot/7‐pole wound field flux switching machine (WFFSM).